Absence of Streptococcus pneumoniae in pharyngeal swabs of geriatric inpatients. Issue 7 (July 2015) - Jomrich, Nina; Kellner, Silvia; Djukic, Marija; Eiffert, Helmut; Nau, Roland
Abstract: Colonization of the pharynx by Streptococcus pneumoniae was studied in 185 in-hospital geriatric patients (median age 81 years) from 29 March 2011 to 22 June 2011. Swabs were plated on blood agar plates. Colonies with a morphology suggesting S. pneumoniae were further analyzed. Surprisingly, pneumococci were not found in any of the samples. Pneumococci chronically colonizing the pharynx of elderly people may be much rarer than previously thought and probably are not the source of pneumococcal pneumonia in old age.